(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article examines the current state of the regulatory framework for accounting in Uzbekistan and its alignment with International Financial Reporting Standards (IFRS). It explores the challenges and opportunities involved in adopting IFRS and proposes strategies for improving the regulatory environment to enhance financial transparency and attract foreign investment. The study emphasizes the importance of a robust regulatory framework in fostering economic growth and integration into the global economy.